Ammonia‐oxidizing archaea and nitrite‐oxidizing nitrospiras in the biofilter of a shrimp recirculating aquaculture system. Issue 1 (9th August 2012) - Brown, Monisha N.; Briones, Aurelio; Diana, James; Raskin, Lutgarde
Abstract This study analysed the nitrifier community in the biofilter of a zero discharge, recirculating aquaculture system (RAS) for the production of marine shrimp in a low density (low ammonium production) system. The ammonia‐oxidizing populations were examined by targeting 16S rRNA and amoA genes of ammonia‐oxidizing bacteria (AOB) and archaea (AOA). The nitrite‐oxidizing bacteria (NOB) were investigated by targeting the 16S rRNA gene. Archaeal amoA genes were more abundant in all compartments of the RAS than bacterial amoA genes. Analysis of bacterial and archaeal amoA gene sequences revealed that most ammonia oxidizers were related to Nitrosomonas marina and Nitrosopumilus maritimus. The NOB detected were related to Nitrospira marina and Nitrospira moscoviensis, and Nitrospira marina‐type NOB were more abundant than N. moscoviensis‐type NOB. Water quality and biofilm attachment media played a role in the competitiveness of AOA over AOB and Nitrospira marina‐over N. moscoviensis‐type NOB.